Prospects of Promoting Festival Tourism: A Case study of Khame Jatra in Bhaktapur - Dulal, Lok Nath (Nepalese Culture, 2022)
Bhaktapur is one of the ancient and the most famous cultural tourist destinations of Nepal. One can observe and have a wonderful experience of tangible and intangible cultural tourism products such as historical, archeological, religious and secular monuments, treasures of arts and crafts and varied indigenous living cultural activities. As the mirrors of Bhaktapur, tangible and intangible cultural heritage reflect the folktales, music and dance, history and traditions, way of life, religious beliefs, costumes and customary laws, dress/ ornaments, social harmony, joys and fears, dreams and sorrows, and the feeling of unity in the diversity of people. The people of Bhaktapur annually celebrate different colourful festivals and Jatras on the special auspicious days. Rest of them, Khame Jatra is a renowned cultural heritage and a very important cultural tourism product. Khame is a male buffalo which is taken out in Open Street for the procession during the ninth day of Dashain festival. It is an archetypal Jatra which is considered a hallmark of indigenous cultural identity and a popular cultural tourism product of Bhaktapur. But, this Jatra is still unexposed; hence it is a hidden or veiled festival. It is necessary recognizing the prominence of Khame Jatra as a prominent tourism product and a prodigious agent for preservation of traditional culture and an effective means of cultural renovation, national identity building and economic growth. The concerned stakeholders and the governing bodies should pay adequate attention for the protection and promotion of this Jatra as a prominent tourism product